The arbitral nature of the Dispute Resolution Chamber : discussion on the necessary requirements for the decisions of the FIFA Dispute Resolution Chamber to be recognized as arbitration awards - Sousa, Pedro Henrique Bandeira (2019)
This dissertation aims to initiate a discussion on the nature of the decisions issued by the FIFA Dispute Resolution Chamber so that they can be enforced, or not, by the New York Convention of 1958. The subject is practically pacified by both jurisprudence and doctrine. However, in order to carry out the analysis and discussion of the theme, the reasons that led to the current understanding, developed since the mid-1990s, should be reviewed and analyzed again, under the current perspective. The purpose of this paper is to show that the scenario that existed when the concept was created, and that has consolidated over the years is different from the current scenario of the DRC. In order to achieve this objective, I will analyze and debate the cases related to this matter, as well as cases of the Swiss Supreme Court, of countries important to the debate and of the Court of Arbitration for Sport - CAS, as well as the doctrinal understanding on the subject and the sports and arbitration legislations. The idea for the discussion started with the analysis of a real case, in Ukraine. After the dispute resolution proceedings in the FIFA Dispute Resolution Chamber, which rendered a favorable award, it did not have a satisfactory outcome due to the lack of enforceability in this particular case. The first part will show the structure of FIFA and the Dispute Resolution System. The second part will analyze the matter of arbitration and the current relationship between arbitration and FIFA. The third part will analyze what is necessary for the formation of an arbitral tribunal and the relationship of the DRC with those requirements. Finally, it will be concluded whether or not it is possible to consider the decisions of the DRC as being arbitral.